i need to change = -3x^2+x-2 to standard form( a(x-p)^2 +q)
can anyone show me the algebraic steps through completing the square?
this is the details
$\displaystyle ax^{2}+bx+c=0$
$\displaystyle x^{2}+\frac{b}{a}x+\frac{c}{a}=0$
$\displaystyle \left( x^{2}+\frac{b}{a}x+\frac{b^{2}}{4a^{2}}\right) +\frac{c}{a}%
-\frac{b^{2}}{4a^{2}}=0$
$\displaystyle \left( x+\frac{b}{2a}\right) ^{2}+\frac{c}{a}-\frac{b^{2}}{4a^{2}}=0$
$\displaystyle \left( x+\frac{b}{2a}\right) ^{2}+\frac{4ac-b^{2}}{4a^{2}}=0$
here's what u need,
Homeomath : forme canonique de ax˛ + bx + c
forget about the writing